Carole Sweeney. Michel Houellebecq and the Literature of Despair. New York: Bloomsbury, 2013. xx + 215 pp. - Benn E Williams (Studies in 20th & 21st Century Literature, 2017)
Review of Carole Sweeney. Michel Houellebecq and the Literature of Despair. New York: Bloomsbury, 2013. xx + 215 pp.
Keywords: biopolitical neoliberalism; capitalism; despair; economic and social liberation; literature